The Mathematical Model of Conductance Measurement in Growing Thin Films - Sinkevičius, V. (Elektronika ir Elektrotechnika, 2008)
The island stage, mono–atomic layers or self–organized derivatives are derivable producing nanostructures by vacuum technology. These layers are too thin for traditional measurements of their resistance or thickness. The non–invasive measurement was proposed for the measurement of these stages. The mathematical model of the non–invasive measurement of the condensate resistance, taking into account the potential distribution in the surface of the measurement probe, was created. Ill. 4, bibl. 7 (in English; summaries in English, Russian and Lithuanian).